Sosialisasi dan Penerapan Teknologi Speed Bump Berbahan Dasar Plastik untuk Lalu Lintas Jalan - Iwan Nugraha Gusniar; Reza Setiawan; Milliyantri Elvandari; Vera Pangni Fahriani; Rikky Rifaldy (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
PkM Tanjung Bungin Village, Karawang Regency is inhabited by 891 families or around 2,612 residents. Crowded places such as entertainment venues, sales of fishermen's catches and traditional markets are always busy with people from villages, sub-districts and even Bekasi Regency. Frequent interaction between the people of Tanjungbungin Village and people outside the village area because of the necessities of life that need to be met causes a large potential for traffic accidents on the connecting road. Apart from that, the unavailability of speed bumps around roads where there are potential accidents and their lack of self-sufficiency means that speed bumps increase the risk of high traffic accidents. There needs to be a program that can provide the right solution to immediately reduce the potential for traffic accidents. Making speed bump technology made from plastic independently among the community will be the right and effective solution. The plastic speed bump technology that had been made is based on research products and uses the same manufacturing method as that carried out in the research. The method that had been implemented is integration between PkM and student KKN activity programs by means of mentoring, training, and making speed bump technology made from plastic. The output of this community service activity was the creation and implementation of a speed bump made from plastic in Tanjungbungin Village, Pakisjaya District, Karawang Regency.